Typification of Roylean plant names in the genus Aquilegia (Ranunculaceae) - Erst, Andrey S.; Boltenkov, Eugeny V.; Pendry, Colin (Phytotaxa, 2020)
Revision of Himalayan Aquilegia Linnaeus (1753: 533) revealed that some names need typification or clarification. Aquilegia are perennial herbs widely distributed at high elevations in Afghanistan, Pakistan, northern India, Nepal, Bhutan and China (Riedl & Nasir 1991, Rau 1993, Press 2000, Yonekura 2008, Shrestha et al. 2018). The purpose of this paper is to contribute to the stability of the nomenclature by typification of three Aquilegia names described by John Royle (Royle 1834, Lauener 1978). This study is based on a comprehensive investigation of the relevant literature, including protologues. For typification, we examined herbarium material and/or images deposited at E, K and LIV (herbarium codes according to Thiers 2020).